Evaluasi Sistem Pentanahan Kubikel 20 kV Berdasarkan Standar PUIL 2020 dan IEEE Std 80-2013 - Pratama, Yogi Edi; Putra, Dian Eka; Yani, Raden Ahmad (SURYA TEKNIKA, 2026)
The grounding system for the 20 kV switchgear at the Bukit Asam Tanjung Enim town site housing complex (capacity 591,147 kW) plays a crucial role in protecting equipment and personnel from overcurrent faults and touch voltage. This study aims to evaluate the existing conditions, compliance with the PUIL 2020 and IEEE Std 80-2013 standards, factors affecting resistance, and recommendations for improvements. Methods included direct measurements using an ETCR 2100A+ clamp meter, theoretical calculations using the Dwight formula (ρ = 30–35 Ωm), and a comparative analysis of pre- and post-maintenance conditions. The results show that the resistance after maintenance was 0.17–0.91 Ω (average 0.42 Ω), down from 0.91 Ω before maintenance. Theoretical calculations yielded 4.77 Ω (ρ = 30 Ωm). All values were below the maximum limit of 5 Ω, so the system was deemed serviceable and safe. Factors affecting resistance include the condition of the connections, corrosion, soil moisture, and soil resistivity. Routine maintenance proved effective in significantly reducing resistance.